Evolution of salmon lice in response to management strategies: a review. (4th March 2021) - Coates, Andrew; Phillips, Ben L.; Bui, Samantha; Oppedal, Frode; Robinson, Nick A.; Dempster, Tim
Abstract: Ectoparasitic salmon lice ( Lepeophtheirus salmonis ) present a major challenge to Atlantic salmon ( Salmo salar ) aquaculture. The demand for effective louse control has produced diverse management strategies. These strategies essentially impose novel selection pressures on parasite populations, driving the evolution of resistance. Here we assess the potential for salmon lice to adapt to current prevention and control methods. Lice have evolved resistance to at least four of five chemical therapeutants, and use of these chemicals has declined significantly in recent years. The industry has shifted to alternative non‐chemical approaches, yet lice may adapt to these as well. Early research suggests that phenotypic variation exists in the louse population upon which non‐chemical selection pressures could act and that this variation may have a genetic basis. From the existing evidence, as well as an examination of evolutionary processes in other relevant parasite and pest systems, we conclude that the evolution of non‐chemical resistance is an emergent concern that must be considered by the industry. We recommend areas for focused research to better assess this risk. It is also important to determine whether phenotypic shifts in response to non‐chemical selection may shift the ecological niche of the parasite, as this may have cascading effects on wild salmon populations. We also recommend further research to identify strategy combinations that have antagonistic selective effects that slow louse evolution and those with synergistic effects that should be avoided. Greater understanding of evolutionary processes can inform aquaculture policies that counteract the rise of resistant parasite populations.